2018
DOI: 10.1037/dev0000535
|View full text |Cite
|
Sign up to set email alerts
|

The development of intergroup resource allocation: The role of cooperative and competitive in-group norms.

Abstract: The present study investigated age-related changes in the intergroup allocation of resources depending on whether the ingroup norm was competitive or cooperative. Participants included children ( = 8.69), adolescents ( = 13.81), and adults ( = 20.89), ( = 263) who were inducted into simulated groups and informed about an ingroup norm of either cooperation or competition. The goal context for the resource allocation task was either prosocial (to benefit the welfare of animals in a charity event) or group focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Whilst the group norm manipulation was based on a number of studies that have successfully shown that children as young as seven years old understand such messages (McGuire et al ., , ; Nesdale & Dalton, ), future replications could consider including a manipulation check to verify that all participants understand the norm message. Further, it would be useful to include a group identification measure in order to ensure the in‐group induction phase of the protocol successfully engendered feelings of in‐group identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the group norm manipulation was based on a number of studies that have successfully shown that children as young as seven years old understand such messages (McGuire et al ., , ; Nesdale & Dalton, ), future replications could consider including a manipulation check to verify that all participants understand the norm message. Further, it would be useful to include a group identification measure in order to ensure the in‐group induction phase of the protocol successfully engendered feelings of in‐group identification.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents are more likely than children to simultaneously consider both issues of morality and group identity. For instance, in recent resource allocation research adolescents engaged in more complex reasoning than children, considering in‐group norms when prioritizing different moral or social goals (McGuire, Manstead, & Rutland, ; McGuire, Rizzo, Killen, & Rutland, ). Given this developmental shift in consideration of peer groups and moral concerns across social contexts, we tested for differences in resource allocation decisions between children (7–11 years old) and adolescents (13–16 years old).…”
Section: Introductionmentioning
confidence: 99%
“…It is consistent with McGuire et al . (), who demonstrated that fairness concerns become more important in intergroup resource allocations with age. A possible explanation for this increase in normative decision‐making is in age‐related increases in the willingness to prioritize moral concerns over non‐moral concerns (such as self‐interest).…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that collaboration between children did not make them more prosocial towards their partners but keener to establish equity when sharing the outcome of their collaboration, providing support for the equity hypothesis and discounting the generosity hypothesis . Finally, studying resource allocations between groups, McGuire, Rizzo, Killen, and Rutland () found that children tried to maximize the realization of prosocial goals, whereas adolescents and adults strictly followed fairness concerns and allocated resources equally between ingroup and outgroup. Thus, the relative importance of prosocial and fairness motivation for demonstrating unselfish behaviour may not be constant but shift over the course of development.…”
Section: Introductionmentioning
confidence: 99%
“…The former approach includes categories that even young children are likely to be familiar with, such as gender, economic status, race, nationality, religion, and language (Bennett et al, 2004;Doyle & Aboud, 1995;Rutland, 1999;Shutts, Brey, Dornbusch, Slywotzky, & Olson, 2016). In contrast, the latter approach involves randomly assigning individuals to novel social groups (McGuire, Rizzo, Killen, & Rutland, 2018;Yee & Brown, 1992). One common variant of the novel social category approach, minimal groups, requires that the basis for group categorization be value-neutral and that the groups be of equal status and not in competition with each other (Dunham, Baron, & Carey, 2011).…”
Section: Investigating Children's Group Preferencesmentioning
confidence: 99%